Uma arquitetura de software interativo para apoio à decisão na modelagem e análise do tráfego urbano - Jradi, Walid Abdala Rfaei (2008)
The present work proposes an architecture of a Decision Support System for modelling, simulating and visualizing urban traffic, using a mathematical model adjusted to the reality of the Brazilian transit, as well as an appropriate choice of data for this context. To prove the viability of the architecture, an interactive tool, called PET-Gyn, was implemented, with a Web graphical interface. The simulation of the traffic was based on algorithms already existing in the literature, with proven effectiveness, but with adaptations that had been shown necessary. The data applied to the urban traffic is composed of information obtained from GoogleMaps API, data on the road mesh and the collection of the traffic demands measured in a region of the city of Goiânia-GO. The tool allows the visualization of basic information about the traffic in a city and offers forms of interaction to simulate the effect of possible reorganizations of the road net.